Spread of Traditional Medicines in India - R. Srinivasan PhD; V. Raji Sugumar PhD (SAGE Publishing, 2017)
For the first time, we have a comprehensive database on usage of AYUSH (acronym for Ayurveda, naturopathy and Yoga, Unani, Siddha, and Homeopathy) in India at the household level. This article aims at exploring the spread of the traditional medical systems in India and the perceptions of people on the access and effectiveness of these medical systems using this database. The article uses the unit level data purchased from the National Sample Survey Organization, New Delhi. Household is the basic unit of survey and the data are the collective opinion of the household. This survey shows that less than 30% of Indian households use the traditional medical systems. There is also a regional pattern in the usage of particular type of traditional medicine, reflecting the regional aspects of the development of such medical systems. The strong faith in AYUSH is the main reason for its usage; lack of need for AYUSH and lack of awareness about AYUSH are the main reasons for not using it. With regard to source of medicines in the traditional medical systems, home is the main source in the Indian medical system and private sector is the main source in Homeopathy. This shows that there is need for creating awareness and improving access to traditional medical systems in India. By and large, the users of AYUSH are also convinced about the effectiveness of these traditional medicines.